Re-Connecting Scholars' Voices: An historical Review of Public Communication in Italy and New Challenges in the Open Government Framework - Gea Ducci (Coordinamento SIBA, 2020)
In an international theoretical framework relating to the challenges of digitalization on public sector communication, the article focuses on the open government process to present a historical review of the public sector communication as it has developed in Italy in the past thirty years. Definitions, reforms and the regulatory framework, structures and competences, different communication approaches and goals are collected here thanks to those "scholars' voices" which have fuelled the scientific debate on communication in public administrations since the 1990s. A diachronic approach is necessary in order to investigate the dynamic nature of the relationship between citizens and public sector organizations in a wider changing context and to further grasp the influence of digital technologies, with their impact on communication strategies and paradigms. The focus of the contribution is on the challenges that communication is facing in the new digital environment and in the contemporary scenario of open government. As the authors underline, the use of digital media is often seen as functional both to promoting a culture of transparency, openness and accessibility and to overcoming the traditional limits of the bureaucratic organizations, but there are some opportunities and risks to consider. So, the final part of the article offers a reflection on the consequences of digitalization. It introduces some key aspects of the contemporary debate on public sector communication in general and specifically in Italy, offering a critical discussion on those topics – new skills and professional profiles, training programmes, internal management, multichannel strategies, etc. - that are revealing their complexity in the new relational and organizational context.